2017
DOI: 10.1136/bmjopen-2016-015672
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of renal denervation for Chinese patients with resistant hypertension using a microirrigated catheter: study design and protocol for a prospective multicentre randomised controlled trial

Abstract: IntroductionAvailable data show that approximately 8%–18% of patients with primary hypertension will develop resistant hypertension. In recent years, catheter-based renal denervation (RDN) has emerged as a potential treatment option for resistant hypertension. A number of observational studies and randomised controlled trials among non-Chinese patients have demonstrated its potential safety and efficacy.Methods and analysisThis is a multicentre, randomised, open-label, parallel-group, active controlled trial t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Reports have shown that the renalase knockout mouse is hypertensive and exquisitely sensitive to cardiac ischemia (Wu et al, 2010), and develops renal tubular damage that can be ameliorated with recombinant renalase treatment (Lee et al, 2013). The administration of recombinant renalase produces a powerful and rapid hypotensive effect on rats (Schiffrin et al, 2007;Wang et al, 2017) and reduces plasma NE, left ventricular hypertrophy (LVH), and cardiac fibrosis in 5/6 nephrectomy hypertensive CKD rats (Baraka and El Ghotny, 2012). Blood renalase levels are inversely correlated with GFR and are markedly reduced in ESRD patients (Desir, 2009).…”
Section: Sympathetic Nervous System Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Reports have shown that the renalase knockout mouse is hypertensive and exquisitely sensitive to cardiac ischemia (Wu et al, 2010), and develops renal tubular damage that can be ameliorated with recombinant renalase treatment (Lee et al, 2013). The administration of recombinant renalase produces a powerful and rapid hypotensive effect on rats (Schiffrin et al, 2007;Wang et al, 2017) and reduces plasma NE, left ventricular hypertrophy (LVH), and cardiac fibrosis in 5/6 nephrectomy hypertensive CKD rats (Baraka and El Ghotny, 2012). Blood renalase levels are inversely correlated with GFR and are markedly reduced in ESRD patients (Desir, 2009).…”
Section: Sympathetic Nervous System Activitymentioning
confidence: 99%
“…The procedure itself ( Figure 2 ) involves the use of catheter-based devices that ablate the renal afferent and efferent (sympathetic) nerves surrounding the renal arteries using either radiofrequency, ultrasound energy, or trans-arterial injection of caustic substances ( Gajulapalli et al, 2020 ). Several trials have been conducted ( Krum et al, 2009 ; Investigators, 2010 ; Esler et al, 2012 ; Kandzari et al, 2012 ; Bakris et al, 2014 ; Bhatt et al, 2014 ; Liu et al, 2017 ; Sievert et al, 2017 ; Böhm et al, 2020 ), however to date, there is no global census or legislative approval of renal denervation as a clinical procedure for the treatment of hypertension non-pharmacologically. Although renal denervation has played an ameliorating role in reducing elevated BP and preserving renal function in diseased kidneys in humans ( Hering et al, 2012 ; Ott et al, 2015 ) and rats ( Yao et al, 2017 ) with CKD, other factors contributing to BP elevation remain, that are unalterable by renal denervation.…”
Section: Pathogenesis Of Hypertension In Chronic Kidney Diseasementioning
confidence: 99%